Dynamic programming of atrioventricular delay improves electrical synchrony in a multicenter cardiac resynchronization therapy study. - Thibault, Bernard; Ritter, Philippe; Bode, Kerstin; Calò, Leonardo; Mondésert, Blandine; Mangual, Jan O.; Badie, Nima; McSpadden, Luke C.; Pappone, Carlo; Varma, Niraj (Heart Rhythm, 2019)
Background: Patient-specific programming of cardiac resynchronization therapy (CRT) is often neglected, despite significant nonresponse rates. The device-based SyncAV CRT algorithm dynamically adjusts atrioventricular delays to the intrinsic AV interval, reduced by a programmable offset, to accommodate each patient's changing needs.Objective: The purpose of this study was to evaluate the acute effect of biventricular (BiV) pacing enhanced by SyncAV on electrical synchrony in a broad patient population.Methods: Patients with existing CRT implants were prospectively evaluated at 5 international centers. Blinded 12-lead electrocardiographic QRS duration (QRSd) measurements were used to compare intrinsic conduction with nominal BiV pacing, BiV + SyncAV (default 50 ms offset), and BiV + SyncAV (optimized, patient-specific offset). BiV configurations were tested twice using the latest activating and earliest activating left ventricular (LV) electrodes as cathodes.Results: Ninety patients (mean age 67.1 ± 9.5 years; 67 (74%) men; 55 (63%) with left bundle branch block; 37 (43%) with ischemic cardiomyopathy; LV ejection fraction 32% ± 9%) with intact atrioventricular conduction (PR interval 195 ± 45 ms) were enrolled. With BiV pacing from the latest activating LV electrode, the intrinsic QRSd of 155 ± 29 ms was reduced by 9% ± 20% to 138 ± 27 ms using traditional BiV pacing and by 13% ± 14% to 133 ± 25 ms using BiV + SyncAV (50 ms offset). The maximal QRSd reduction by 20% ± 10% to 123 ± 22 ms was achieved by BiV + SyncAV with an optimized offset. Similar QRSd reductions were observed with BiV pacing from the earliest activating LV electrode across all settings. Of all baseline characteristics, intrinsic QRSd was the only significant predictor of QRSd reduction magnitude.Conclusion: SyncAV improved acute electrical synchrony beyond conventional CRT, particularly with patient-specific optimization. The degree of synchrony restored was contingent on intrinsic QRSd, but not limited by other baseline characteristics or by the LV pacing electrode used.